Jumlah Kredit dan Suku Bunga terhadap Profitabilitas dengan Kualitas Kredit sebagai Pemoderasi - Ardiyani, Ni Kadek Winda; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 33 No 1 (2023), 2023)
Profitability is very important for a company because it is one of the bases used to assess the condition of a company. The purpose of this study was to obtain empirical evidence regarding the effect of the amount of credit extended and interest rates on profitability with credit quality as a moderator. This research was conducted at LPD in Buleleng Regency. The number of samples taken using the non-probability sampling method with purposive sampling technique obtained as many as 42 samples. Data collection was carried out using non-participant observation methods with documentation techniques. The analysis technique used is multiple linear regression and Moderated Regression Analysis. According to the findings of the data analysis, the amount of credit distributed has a positive and significant effect on profitability and interest rates have no significant effect on profitability. This study also shows that credit quality weakens the influence of the amount of credit extended and interest rates on profitability. Keywords: Profitability; Interest Rate; Credit Quality